Estimación de saturaciones in-situ durante experimentos de inyección de fluidos usando tomografía computarizada de rayos X (2017)
X-rays computed tomography (CT) imaging during coreflooding experiments, allows monitoring fluid flow in porous media and quantitative and semi-quantitative analysis, which contribute to a better understanding of the phenomena being studied in the laboratory. This paper presents the necessary procedure, equipment and considerations for the correct acquisition and interpretation of these images during different laboratory tests. Subsequently it presents the development of a coreflooding experiment and the analysis of accuracy of the results obtained by the images interpretation and its possible applications. Results show a good agreement between CT saturations and material balance saturations.